Use of cannabis sativa. L derivatives. in adjuvant treatment in oncological patients in the city of Caruaru, Pernambuco (Research, Society and Development, 2021)
In the current context, the medicinal use of cannabis derivatives has taken on increasing proportions. However, although medicinal use has obtained a significant increase in recent years and legal approval for its use legally in Brazil, knowledge and use of this therapeutic option is still not a reality. One of the biggest obstacles is the bureaucracy for accessing medicines or products. In view of the therapeutic rise of Cannabis Sativa drugs and products in Brazil and worldwide, this article aimed to carry out a survey through a quantitative-descriptive field study in cancer centers in the city of Caruaru-PE to investigate the positioning of physicians and the multidisciplinary team in relation to the products in question to help with cancer treatment; what is their knowledge about this therapeutic option, as well as making a parallel with the existing drugs and the bureaucracy to have access to Cannabis Sativa derivatives. Based on the results, the use of the drug in question pointed to a neutrality of professionals involved in the oncology area.